The leisure paradox for entrepreneurs: A neo-institutional theory perspective of disclosing leisure activities in crowdfunding pitches - Waddingham, Jacob A.; Chandler, Jeffrey A.; Alexander, Katherine C.; Zafar, Sana; Anglin, Aaron (Journal of Business Venturing, 2025)
Drawing from neo-institutional theory, we examine how entrepreneurs' disclosure of leisure activities influences the performance of their crowdfunding campaigns. We propose that entrepreneurs' disclosure of leisure activities in their campaigns negatively impacts crowdfunding performance because an institutional norm exists pressuring early-stage entrepreneurs to conform to workaholism. Using a sample of 8511 Kickstarter campaigns and a randomized experiment (n = 436), we find evidence that entrepreneurs who disclose leisure activities are viewed as less workaholic. This, in turn, hurts backers' perceptions of the entrepreneurs' legitimacy, leading to lower crowdfunding performance. We also find women backers are more tolerant of entrepreneurs disclosing their leisure activities than men.